IMPLEMENTASI PROGRAM 'AMALIYAH TADRIS UNTUK PENINGKATAN MUTU LEMBAGA DI MADRASAH 'ALIYAH (MA) TARBIYATUL MU'ALLIMAT AL-ISLAMIYAH (TMAI) AL-AMIEN PRENDUAN MADURA - Muhairira, Nur Jamilatul (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
The The implementation of the 'Amaliyah Tadris' program is an implementation of teaching practice activities carried out from planning to evaluation with the aim of female students at Tarbiyatul Mu'llimat (TMaI) Prenduan Sumenep Madura being able to become teachers as in the word tarbiyah, so that with this the output is The results produced will be of high quality and of course will have an influence on the quality of the institution. So before carrying out this program, you must be prepared with thorough preparation starting from planning to evaluating this program, and the activities will run according to the objectives. The focus of this research is: 1) how to plan the 'Amaliyah Tadris program to improve the quality of institutions at Madrasah 'Aliyah (MA) Tarbiyatul Mu'allimat Al-Islamiyah (TMaI) Al-amien Prenduan Madura, 2) how to implement the 'Amaliyah Tadris program to improve quality of institutions at Madrasah 'Aliyah (MA) Tarbiyatul Mu'allimat Al-Islamiyah (TMaI) Al-amien Prenduan Madura, 3) what are the results of the 'Amaliyah Tadris program to improve the quality of institutions at Madrasah 'Aliyah (MA) Tarbiyatul Mu'allimat Al- Islamiyah (TMaI) Al-amien Prenduan Madura. This research uses a qualitative approach, where in this case the researcher really understands the phenomena that occur and in maintaining the authenticity of the data the researcher is actively involved and goes directly to the field. The results of the research are: 1) the planning used in the 'amaliyah tadris program is by understanding basic science, i'dad tadris, 'amaliyah tadris an-namudzajiah and teaching experiments, 2) implementation of the 'amaliyah tadris program starting from the opening, delivery of the material and giving questions related to the material, 3) the results of the 'amaliyah tadris program make the female students skilled in teaching, practicing public speaking and increasing their self-confidence and creating quality graduates